Unusual paraendocrinal mask of lung cancer - Ścieszka, Maria; Ścieszka, Ewa (Contemporary Oncology/Współczesna Onkologia, 2004)
The case of a syndrome of inappropriate antidiuretic hormone secretion (SIADH) in a patient with insidious course of small-cell lung cancer is reported. Some pathologic changes are indirectly caused by the present malignancy; they are defined as paraneoplastic syndromes. They are caused by the release of substances (released from tumor cells because of the changed genetic information) acting as hormones or cytokines. A woman with recurrent psychiatric disorders and several other non- -specific symptoms like weakness, vomiting, mild hypertension was admitted to psychiatric ward twice. After several weeks, a constantly decreasing level of Na+ (hyponatremia) observed at the internal ward suggested that the above symptoms can only be a manifestation of paraneoplastic syndrome in the form of SIADH resulting in hyponatremia (causing oedema of CNS and typically all disorders listed above). Our aim was to explain how the presence of some easily diagnosed symptoms should make us suspect this particular manifestation of paraneoplastic syndrome. We wanted to emphasise the need of being aware that some non-specific, trivial symptoms can be a mask of the neoplastic process. When those symptoms blur the manifestation of a cancer itself it can lead to misdiagnosis, implicates improper therapeutic decisions and deteriorates prognosis.